Evaluation of pre-selected mandarin hybrids based on tolerance to alternaria brow spot, physicochemical characteristics and acceptability - Moura, Vanessa Santos; Verruma-Bernardi, Marta Regina; Rodrigues, Josiane; Cristofani-Yaly, Mariângela; de Azevedo, Fernando Alves; Bastianel, Marinês (Frontiers in Food Science and Technology, 2025)
The selection of new mandarin varieties to enhance fruit supply and address phytosanitary challenges is a significant issue in table citrus farming. In Brazil, the primary harvest season for commercial varieties spans from May to August, leaving a gap in the availability of mandarins during the off-season, which typically coincides with the hottest months of the year. Furthermore, diseases such as Alternaria Brown Spot (ABS) and HLB have reduced planted areas due to the complexities of management and increased production costs. This study evaluated three new mandarin hybrids based on tolerance for ABS, their physicochemical properties and acceptance. Although citrus researchers’ experts of mandarins conducted the sensory characterization, the methodology reflects sensory descriptions grounded in consumer perception. Providing detailed data for each mandarin hybrid is crucial, as the varieties exhibit distinct characteristics that influence overall evaluations and help align each hybrid with consumer expectations. The results demonstrate that, despite variations in acceptance among evaluators for one or more attributes ranking from “slightly liked” to “liked a lot,” all hybrids were generally well received. Such studies are vital for guiding the selection of new mandarin varieties in genetic improvement programs.